Effect of Text Messaging Plus Peer Navigation on Viral Suppression Among Youth With HIV in the iCARE Nigeria Pilot Study. (1st August 2021) - Taiwo, Babafemi O.; Kuti, Kehinde M.; Kuhns, Lisa M.; Omigbodun, Olayinka; Awolude, Olutosin; Adetunji, Adedotun; Berzins, Baiba; Janulis, Patrick; Johnson, Amy K.; Okonkwor, Ogochukwu; Oladeji, Bibilola D.; Muldoon, Abigail; et al.
Abstract : Background: Consistent with the global trend, youth with HIV (YWH) in Nigeria have high rates of viral nonsuppression. Hence, novel interventions are needed. Setting: Infectious Diseases Institute, College of Medicine, University of Ibadan, Nigeria. Methods: In a single-arm trial, participants aged 15–24 years received 48 weeks of a combination intervention, comprising daily 2-way text message medication reminders plus peer navigation. The primary outcome measure was viral suppression less than 200 copies/mL. The secondary outcome measures included self-reported adherence on a visual analog scale and medication possession ratio, each dichotomized as ≥90% (good) or <90% (poor) adherence. The outcomes were analyzed using McNemar test. Retention in care, intervention feasibility and acceptability, and participants' satisfaction were also assessed. Results: Forty YWH (50% male participants) were enrolled: mean age 19.9 years (SD = 2.5), 55% perinatally infected, and 35% virologically suppressed at baseline. Compared with baseline, the odds of virologic suppression was higher at 24 weeks (odds ratio = 14.00, P < 0.001) and 48 weeks (odds ratio = 6.00, P = 0.013). Self-reported adherence (≥90%) increased from baseline at 24 weeks (63%, P = 0.008) and 48 weeks (68%, P = 0.031). Medication possession ratio ≥90% increased at weeks 24 and 48 (85% and 80%, respectively), achieving statistical significance at 24 weeks alone ( P = 0.022). Retention in care at 48 weeks was 87.5%. All (37/37) participants at week 48 were fully or mostly satisfied with the intervention. Conclusion: Daily 2-way text message reminders plus peer navigation is a promising combination intervention to improve viral suppression among YWH in Nigeria. Abstract : Supplemental Digital Content is Available in the Text.